2019
DOI: 10.2147/cmar.s213419
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects of Matrine in Combination with Docetaxel on Castration-Resistant (Androgen-Independent) Prostate Cancer</p>

et al.

Abstract: Background: Matrine (MAT) exhibits higher efficacy of chemotherapy when it is combined with other chemotherapeutic drugs; however, the therapeutic efficacy of matrine in combination with docetaxel (DOC) for prostate cancer, or even androgen-independent prostate cancer, remains poorly understood and the underlying molecular mechanisms have not yet been clearly defined. In the present study, we investigated whether matrine combined with docetaxel can strengthen anti-cancer effect. Methods: In this study, 7 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Matrine, an active component of Sophora flavescens, has antitumor effects in breast, ovarian, non-small cell lung and colorectal cancers, similarly to that of cisplatin in liver cancer (17)(18)(19). A study by Li et al (20) reported that treatment with matrine in combination with docetaxel inhibits the proliferation and migration of tumor cells in androgen-resistant prostate cancer, indicating the potential antitumor effects of matrine in combination with chemotherapeutic drugs. A previous study from our laboratory demonstrated that matrine in combination with cisplatin exerts a favorable antitumor effect in liver cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Matrine, an active component of Sophora flavescens, has antitumor effects in breast, ovarian, non-small cell lung and colorectal cancers, similarly to that of cisplatin in liver cancer (17)(18)(19). A study by Li et al (20) reported that treatment with matrine in combination with docetaxel inhibits the proliferation and migration of tumor cells in androgen-resistant prostate cancer, indicating the potential antitumor effects of matrine in combination with chemotherapeutic drugs. A previous study from our laboratory demonstrated that matrine in combination with cisplatin exerts a favorable antitumor effect in liver cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Matrine combined with docetaxel could inhibit proliferation, migration and invasion of both DU145 and PC-3 cells in a dose- and time-dependent manner. Matrine have anti-inflammation effects on the DU145 and PC-3 cells ( Li et al, 2019 ).…”
Section: Experimental Researchmentioning
confidence: 99%
“…In terms of nervous system diseases, injecting matrine (30mg/kg) into the jugular vein can inhibit the activity of 12/ 15-lipoxygenase and the expression of NF-κB, TLR4, and TLR2 in ischemic brain tissue [63]. Moreover, it can reduce not only the nerve function defect of right middle cerebral artery occlusion model rats but also the volume of local cerebral infarction.…”
Section: Matrinementioning
confidence: 99%